2011
DOI: 10.1017/s0007114511001188
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARγ and δ by dietary punicic acid ameliorates intestinal inflammation in mice

Abstract: The goal of the present study was to elucidate the mechanisms of immunoregulation by which dietary punicic acid (PUA) prevents or ameliorates experimental inflammatory bowel disease (IBD). The expression of PPARg and d, their responsive genes and pro-inflammatory cytokines was assayed in the colonic mucosa. Immune cell-specific PPARg null, PPARd knockout and wild-type mice were treated with PUA and challenged with 2·5 % dextran sodium sulphate (DSS). The prophylactic efficacy of PUA was examined in an IL-10 2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 55 publications
3
58
0
Order By: Relevance
“…Our results (Figs. 4 and 6A) are consistent with previous findings that inhibition of TNF-a release consecutively inhibits the increased level of iNOS and subsequent colonic damage and inflammation in a murine colitis model (Cho et al, 2010;Colon et al, 2001;Má rquez et al, 2010;Kumar et al, 2011;Bassaganya-Riera et al, 2011). IL-1b and IL-6 are other key mediators of the progression of IBD.…”
Section: Discussionsupporting
confidence: 90%
“…Our results (Figs. 4 and 6A) are consistent with previous findings that inhibition of TNF-a release consecutively inhibits the increased level of iNOS and subsequent colonic damage and inflammation in a murine colitis model (Cho et al, 2010;Colon et al, 2001;Má rquez et al, 2010;Kumar et al, 2011;Bassaganya-Riera et al, 2011). IL-1b and IL-6 are other key mediators of the progression of IBD.…”
Section: Discussionsupporting
confidence: 90%
“…Due to potential side effects, the application of RSG in the treatment of IBD is not likely ( 61,62 ). Efforts toward the discovery of a new class of PPAR ␥ agonist that elicits therapeutic effects against IBD with limited or no adverse side effects revealed that conjugated linoleic acid (CLA) is a safer alternative to RSG in the model of spontaneous pan-enteritis and DSS-induced colitis (63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies showed that PSO is able to reduce tumor occurrence in both ex vivo and in vivo rodent models (29,35,43). In addition, recent studies indicate that PuA ameliorates TNSB-and DSS-induced colitis (2,8).…”
mentioning
confidence: 99%